2015
DOI: 10.3109/14764172.2015.1027224
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periorbital syringoma by the pinhole method using a carbon dioxide laser in 29 Asian patients

Abstract: Our observations indicated that application of the pinhole method using a CO2 laser exerts positive therapeutic effects in Asian patients with periorbital syringomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Current treatments for syringomas include topical and systemic medications, chemical peels, CO2 lasers, electrocautery, and surgery, all of which have shown some relief 6,27–31 . However, in the treatment of eruptive syringomas, the above physical therapy seem not suitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatments for syringomas include topical and systemic medications, chemical peels, CO2 lasers, electrocautery, and surgery, all of which have shown some relief 6,27–31 . However, in the treatment of eruptive syringomas, the above physical therapy seem not suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments for syringomas include topical and systemicmedications,chemicalpeels,CO2lasers,electrocautery,and surgery, all of which have shown some relief. 6,[27][28][29][30][31] However, in the treatment of eruptive syringomas, the above physical therapy seem not suitable. It is easier to leave scars during the operation becauseoflargerasharea.Onthecontrary,thehighcostoftreatment also makes patients give up this option.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al, 2016 [14] CO 2 laser 29 >75% improvement in 24.1% after 2 sessions Lee et al, 2015 [15] Fractional CO 2 laser 35 >75% improvement in 8.6% after 2 sessions Cho et al, 2011 [16] * BoTN -Botulinum toxin most frequently in the head and neck area. As suggested by our own experience, fractional CO 2 laser may be an effective and safe tool to improve facial appearance for the treatment of multiple periocular syringomas that poorly respond to ablative CO 2 laser.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed excellent cosmetic results in 11 patients who were treated with multiple-drilling methods using a CO 2 laser without complications such as scarring, erythema, or pigmentary changes ( Park et al, 2007 ). Another prospective study using a pinhole method with an ablative 10,600 nm CO 2 laser on the periorbital skin showed minimal improvement (0 to 25%) in 4 patients (13.8%), moderate improvement (26-50%) in 8 patients (27.6%), marked improvement (51-75%) in 10 patients (34.5%), and near-total resolution (> 75%) in 7 patients (24.1%; Lee et al, 2015c ). Patients with vulvar syringomas have also been successfully treated with a CO 2 laser ( Huang et al, 2003 ).…”
Section: Syringomasmentioning
confidence: 97%